IOT-BASED STANDING WATER MONITORING SYSTEM FOR SUPPORTING PREVENTIVE MAINTENANCE IN AIRPORTS - Rehan Zikri Avian; Yayuk Suprihartini (Journal of Airport Engineering Technology (JAET), 2026)
Standing water on airport runways may reduce aircraft braking performance and increase the risk of hydroplaning during takeoff and landing. This study developed an IoT-based standing-water monitoring prototype to support preventive maintenance at Sultan Mahmud Badaruddin II International Airport in Palembang. An R&D method was applied. The system integrated JSN-SR04T ultrasonic sensors, GPS, Raspberry Pi, Arduino, and a camera with U-Net image segmentation, all connected to a web dashboard via HTTP. The dataset consisted of 1,200 runway water images divided into training (70%), validation (20%), and testing (10%) sets. Testing showed that the ultrasonic sensor achieved optimal accuracy at water depths above 2 cm, while the camera detected clear water up to 1.5 m and turbid water up to 2 m. User validation with five expert respondents yielded a feasibility score of 91%, categorized as excellent.